Dehydrogenative Coupling of a Tertiary Silane Using Wilkinson's Catalyst. Issue 18 (28th June 2016) - Azpeitia, Susan; Fernández, Belén; Garralda, María A.; Huertos, Miguel A.
Abstract: Invited for the cover of this issue is the group of Miguel A. Huertos at Universidad del País Vasco, San Sebastián, Spain. The cover image shows the dehydrocoupling of a tertiary silane catalyzed by Wilkinson's catalyst. The hydrosilane used as substrate in this reaction has two thioether moieties, which help synthesize an active species in the catalytic cycle, such as the silylhydridorhodium(III) complex also shown. Abstract : This is the first example of the dehydrocoupling of a tertiary silane with a rhodium catalyst… Read more about the story behind the cover in the Cover Profile and about the research itself onp. 2891 ff .